Using vertical jump power and standing long jump power to determine muscle imbalance - Konz, S. M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this investigation was to determine the relationship between a ratio between vertical jump (VJ) power and standing long jump (SLJ) power and knee injury risk by using the functional power outputs with information generated from knee isokinetic testing. Medical records along with strength and conditioning testing records of 13 female NCAA-I soccer athletes were examined. Correlation and linear regressions were run to find relationships. The medical records included the isokinetic knee flexion and extension testing. Data from VJ height and SLJ distance were taken from the strength and conditioning data. Using VJ and SLJ power results to determine tendency in muscle dominance would allow development of interventions tailored to decrease the imbalance.